Carbon Monoxide Gas Sensing Technologies in Combustion Process - Pavel SHUK (Sensors & Transducers, 2017)
Three major carbon monoxide gas sensing technologies for combustion environment are reviewed with many theoretical and practical aspects, test results as well as basic operation details. A comprehensive CO gas sensing technologies review is supported with the latest development trends. Performance and applications options for carbon monoxide measurements in the process using calorimetric catalytic, mixed potential electrochemical CO-sensor with zirconia solid electrolyte and tunable diode laser (TDL) or quantum cascade lasers (QCL) spectroscopy for CO measurements are discussed for the applications in power generation, chemicals production, heating, process control, safety, and quality. Special attention is given to the technologies application limits and analyzer’s system requirements.